Identification of Potential Pathogenic Super-Enhancers-Driven Genes in Pulmonary Fibrosis - Li, Hang; Zhao, Caiping; Li, Zeli; Yao, Kainan; Zhang, Jingjing; Si, Wenwen; Liu, Xiaohong; Jiang, Yong; Zhu, Meiling (Frontiers in Genetics, 2021)
Abnormal fibroblast differentiation into myofibroblast is the crucial pathological mechanism of pulmonary fibrosis (PF). Super-enhancers, a newly discovered cluster of regulatory elements, are regarded as the regulators of cell identity. We speculate that abnormal activation of super-enhancers must be involved in the pathological process of PF. This study aims to identify potential pathogenic super-enhancers-driven genes in PF. Differentially expressed genes (DEGs) in PF mice lungs were identified from the GEO dataset (GDS1492). We collected super-enhancers and their associated genes in human lung fibroblasts and mouse embryonic fibroblasts from SEA version 3.0, a network database that provides comprehensive information on super-enhancers. We crosslinked up-regulated DEGs and super-enhancers associated genes in fibroblasts to predict potential super-enhancers-driven pathogenic genes in PF. A total of 25 genes formed into overlap and the protein-protein interaction network of these genes were constructed by the STRING database. An interaction network of transcription factors (TFs), super-enhancers, and associated genes was constructed using Cytoscape software. Gene enrichment analyses, including KEGG pathway and GO analysis, were performed for these genes. Latent transforming growth factor-beta binding protein 2 (LTBP2), one of the predicted super-enhancers-driven pathogenic genes was used to verify the predicted network's accuracy. LTBP2 up-regulated in the lungs of the bleomycin-induced PF mice model and TGF-β1-stimulated mouse and human fibroblasts. Myc is one of the TFs binding to LTBP2 super-enhancer. Knockout of super-enhancer sequences with CRISPR/Cas9 plasmid or inhibition of Myc all decreased TGF-β1-induced LTBP2 expression in NIH/3T3 cells. Identifying and interfering super-enhancers might be a new way to explore possible therapeutic methods for PF.